Kajian Literatur: Evaluasi Cara Distribusi Obat Yang Baik (CDOB) Pada Sarana Distribusi Obat - Luthfanto Hafizhuddin; Ni Made Amelia Ratnata Dewi; Iman Surya Pratama (Unram Medical Journal, 2022)
There has been an increase in studies related to good distribution practices (GDP) in recent years. However, the literature review exploring GDP evaluation is limited. Therefore, this scoping review aims to map the current knowledge regarding the implementation of GDP in drug distribution facilities. A literature search was conducted in Google Scholar based on the modified PRISMA protocol. The literature that met the inclusion and exclusion criteria was then extracted into the table. The results of literature extraction show that the overall studies obtained are descriptive; studies are predominantly conducted on pharmaceutical wholesalers and Western Indonesia; regulations that used as references have not been updated; the results of the questionnaire have not been validated and using a small sample. Therefore, studies that can be carried out include looking at the factors that influence the implementation of GDP; explored the level of application of GDP in other distribution channels such as drugstores and Eastern Indonesia, and updated the study with new guidelines. As for validating the results of the questionnaire and using a larger sample of distribution facilities can be used as consideration for further research.